(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes the features of the vitagenic education in the system of pedagogical knowledge. Next will be illustrated the classificational, purposal and conceptual technologies of the vitagenic education. The main point of pedagogical association, subjective personalities and some of the features of vitagenic experiences in education process. Informed about vital experiences of personalities, and the role of intelligent-psychological potential of educational aims.